2012
DOI: 10.1371/journal.pntd.0001561
|View full text |Cite
|
Sign up to set email alerts
|

Reciprocal Tripartite Interactions between the Aedes aegypti Midgut Microbiota, Innate Immune System and Dengue Virus Influences Vector Competence

Abstract: Dengue virus is one of the most important arboviral pathogens and the causative agent of dengue fever, dengue hemorrhagic fever, and dengue shock syndrome. It is transmitted between humans by the mosquitoes Aedes aegypti and Aedes albopictus, and at least 2.5 billion people are at daily risk of infection. During their lifecycle, mosquitoes are exposed to a variety of microbes, some of which are needed for their successful development into adulthood. However, recent studies have suggested that the adult mosquit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

16
346
2
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 333 publications
(366 citation statements)
references
References 31 publications
16
346
2
2
Order By: Relevance
“…Although this had the advantage of providing mosquitoes of known infection status and virus titer, mosquitoes collected in the field will be infected orally and will likely exhibit variable virus titers and analyte accumulation caused by differences in time of extrinsic incubation, permissiveness to DENV infection and replication, and environmental conditions including temperature. 23,32,33 Viral tissue tropisms and load also may be different in intrathoracically infected mosquitoes as compared with orally infected mosquitoes and could affect the efficacy of the respective tests. However, the previous study by Tan and others, 28 which used Bio-Rad's Dengue NS1 Ag Strip test, showed that detection of DENV NS1 antigen was successful for both orally infected and field collected specimens.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although this had the advantage of providing mosquitoes of known infection status and virus titer, mosquitoes collected in the field will be infected orally and will likely exhibit variable virus titers and analyte accumulation caused by differences in time of extrinsic incubation, permissiveness to DENV infection and replication, and environmental conditions including temperature. 23,32,33 Viral tissue tropisms and load also may be different in intrathoracically infected mosquitoes as compared with orally infected mosquitoes and could affect the efficacy of the respective tests. However, the previous study by Tan and others, 28 which used Bio-Rad's Dengue NS1 Ag Strip test, showed that detection of DENV NS1 antigen was successful for both orally infected and field collected specimens.…”
Section: Discussionmentioning
confidence: 99%
“…To address heterogeneity in virus loads likely to be encountered in field-collected mosquitoes caused by differences in vector competence, times of extrinsic incubation, and environmental factors, 23,32,33 mosquitoes harvested 1, 3, 7, 14, or 21 days PI, respectively, were added to the pools of uninfected mosquitoes. Mosquito pools were triturated using cold pestles in 1.5 mL of L-15 medium for pools of 1 and 10 mosquitoes, 2 mL for pools of 100 and 500 mosquitoes, and 3 mL for pools of 1,000 mosquitoes.…”
Section: Methodsmentioning
confidence: 99%
“…1 Recent studies have shown that the microbiota of mosquitoes can affect their ability to become infected with and to vector certain pathogens. [2][3][4][5] There is a growing realization that mosquito populations are naturally infected with a wide range of bacteria, 6,7 fungi, 8 and viruses [9][10][11][12][13][14][15] ; and this recognition has raised interest in the potential effects of these microbes on mosquito ecology and on pathogen transmission.…”
Section: Introductionmentioning
confidence: 99%
“…aegypti mosquitoes on their vector competence for dengue virus have also been demonstrated. 48,49 The concept of "vector competence" has been defined "as the innate ability of a vector to acquire a pathogen and to successfully transmit it to another susceptible host." 50 It is generally accepted that the vector competence of a hematophagous arthropod is influenced by a number of external (extrinsic) and internal (intrinsic) factors, such as temperature, larval nutrition, age, host preference, genetic make-up, and innate immunity.…”
Section: Discussionmentioning
confidence: 99%